Illumina sequencing of the chloroplast genome of common ragweed (Ambrosia artemisiifolia L.) - Erzsébet Nagy; Géza Hegedűs; János Taller; Barbara Kutasy; Eszter Virág (Data in Brief, 2017)
Common ragweed (Ambrosia artemisiifolia L.) is the most widespread weed and the most dangerous pollen allergenic plant in large areas of the temperate zone. Since herbicides like PSI and PSII inhibitors have their target genes in the chloroplast genome, understanding the chloroplast genome may indirectly support the exploration of herbicide resistance and development of novel control methods. The aim of the present study was to sequence and reconstruct for the chloroplast genome of A. artemisiifolia and establish a molecular dataset. We used an Illumina MiSeq protocol to sequence the chloroplast genome of isolated intact organelles of ragweed plants grown in our experimental garden. The assembled chloroplast genome was found to be 152,215 bp (GC: 37.6%) in a quadripartite structure, where 80 protein coding genes, 30 tRNA and 4 rRNA genes were annotated in total. We also report the complete sequence of 114 genes encoded in A. artemisiifolia chloroplast genome supported by both MIRA and Velvet de novo assemblers and ordered to Helianthus annuus L. using the Geneious software. Keywords: Illumina sequencing, Chloroplast genome, cpDNA, Common ragweed, Ambrosia artemisiifolia